From Gutiérrez to Moreno: an analysis of the mobilizations and protests of the Ecuadorian indigenous movement and the state responses to them - Lúcar Oba, León (2020)
The strength of the indigenous movement in Ecuador has proven itself, since the change of century, to be capable of shaping national politics through social pressure and mobilization. From massive protests that toppled presidents, to candidates strategically aligning with CONAIE, the indigenous movement has been consolidated as a central political actor in Ecuador. Nonetheless, the trajectory of its political stances and actions has not been stable, and this variation seems to be explained by the movement’s relationship vis-a-vis the government in office. The present article will briefly go over the governments of Gutiérrez, Correa and Moreno (up to 2019) to establish theoretical frameworks in which the demands of the indigenous movement can be classified, to be able to identify the reasoning behind the different courses of action and incentives for mobilization. Particularly, the analysis will shine light on how national politics create incentives for the Ecuadorian indigenous movement to use its organizational resources to pressure the government.